Ecofisiologia e produtividade de alecrim pimenta nas condições edafoclimáticas do Maciço de Baturité, Ceará - Ribeiro, Maria da Saúde de Sousa (2015)
The medicinal plants are included within the wide diversity of the Maciço de Baturité ecosytem and they are an important component of traditional medicine of this region. However, scientific information that may contribute to the increase in the cultivation of these plants are still rare, particularly at conditions of the State of Ceará. The overall objective of this project is to evaluate the development and the production of alecrim pimenta (Lippia origanoides) at conditions of Maciço de Baturité, Ceará. Two experiments were conducted, the first during the dry season of 2013 (August to November) and the second during the rainy season of 2014 (February to May). The experiment was corned out in completely randomized design with split plots, being the plots defined by two seasons (drought and rainy), the subplot formed by light conditions (greenhouse and full sun), and the subsubplots formed by four evaluation times (0, 40, 80 and 120 days after transplanting). Five replications were used, each one represented by a pot of 20 L containing a plant. The following variables were evaluated: leaf area, plant height, stem diameter, dry matter production, leaf gas exchange, chlorophyll content, mineral nutrients, organic solutes, and essential oils. The alecrim pimenta grows well in the Baturité region, with yields of biomass and essential oil similar to those observed in other studies. The cultivation in greenhouse (50% of solar radiation) changed the pattern of development of alecrim pimenta, resulting in plants with better overall appearance, taller, with larger leaves, higher specific leaf area, less developed root system, and lower root/shoot ratio, regardless of the season of cultivation. The production of dry biomass of leaves and total did not differ between the two environments (light conditions) after 120 days cultivation, regardless of the period of year. During the drought season there was a strong influence of the light condition on stomatal conductance and transpiration, with the values being lower in full sun environment, suggesting stomatal sensitivity to climate conditions in this species. Plants grown in greenhouse showed, in general, higher levels of nutrients and nitrogen compounds (N-aminossolúveis), compared to plants under full sunlight, regardless of the cropping season.